ヒガシ ドロンイングモードランド, セール・ロンダーネ サンチ チガク チョウサタイ ホウコク 2008-2009 (JARE-50) - 大和田, 正明; オオワダ, マサアキ; 志村, 俊昭; シムラ, トシアキ; 柚原, 雅樹; ユハラ, マサキ; 束田, 和弘; ツカダ, カズヒロ; 亀井, 淳志; カメイ, アツシ; 阿部, 幹雄; アベ, ミキオ; et al. (2011)
P(論文) 第50次日本南極地域観測隊(JARE-50)夏隊・セール・ロンダーネ山地地学調査隊は,山地西部地域の地質調査を実施した(国立極地研究所一般研究プロジェクト,P-5-1:代表・本吉洋一).調査地へは,ドロンイングモードランド航空ネットワークを利用して空路ケープタウンから山地に入った.メンバーの構成は,地質調査担当5名とフィールドアシスタント1名である.調査地では三つのキャンプ(ベースキャンプ,前進キャンプ1および前進キャンプ2)を設営し,75日間すべてテントで生活した.本報告では,セール・ロンダーネ山地地学調査隊の設営,西部の気象条件および野外調査結果を含め,調査計画から実施に至る過程について記述する. The Sør Rondane Mountains field party, part of the summer party of the 50th Japanese Antarctic Research Expedition (JARE-50), consisted of five geologists and one field assistant, and conducted geological fieldwork in the western Sr Rondane Mountains, Eastern Dronning Maud Land, as part of a research project of the National Institute of Polar Research (#P-5-1). The field party accessed the mountains using the Dronning Maud Land Air Network (DROMLAN) from Cape Town to a runway close to the Belgian base, via the Novolazarevskaya runway. The field party made three campsites (Base Camp, Camp 1, and Camp 3) and stayed on the snowfield for 75 days. Here, we report the detailed operation plans and present a summary of the fieldwork, including information on logistics and weather reports for the western Sør Rondane Mountains. departmental bulletin paper